2008
DOI: 10.1007/s12011-008-8158-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Trace Metal Distribution and Correlation in Human Malignant and Benign Breast Tissues

Abstract: Selected trace metals were analyzed in human malignant and nonmalignant (benign) breast tissue samples by the flame atomic absorption spectrophotometric method. In malignant tissues, dominant mean concentrations were revealed by Na, K, Ca, Mg, Fe, Zn, and Al at 927, 552, 231, 61.7, 36.5, 18.3, and 8.94 microg/g, respectively, while the mean metal levels in benign tissues were 903, 435, 183, 63.3, 24.7, 14.5, and 10.1 microg/g, respectively. Average concentrations of Cd, Co, Cr, Cu, Fe, Mn, K, Ca, and Zn were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…There were 13 studies including 978 exposed cases and 1279 controls ( Figure 1) (Antila et al, 1996;Ionescu et al, 2006;McElroy et al, 2006;Wu et al, 2006;Pasha et al, 2008;Strumylaite et al, 2008;Gallagher et al, 2010;Benderli Cihan et al, 2011;Saleh et al, 2011;Strumylaite et al, 2011;Kotsopoulos et al, 2012;Nagata et al, 2013). The characterization of all selected studies was summarized in Table 1.…”
Section: Meta-analysismentioning
confidence: 99%
“…There were 13 studies including 978 exposed cases and 1279 controls ( Figure 1) (Antila et al, 1996;Ionescu et al, 2006;McElroy et al, 2006;Wu et al, 2006;Pasha et al, 2008;Strumylaite et al, 2008;Gallagher et al, 2010;Benderli Cihan et al, 2011;Saleh et al, 2011;Strumylaite et al, 2011;Kotsopoulos et al, 2012;Nagata et al, 2013). The characterization of all selected studies was summarized in Table 1.…”
Section: Meta-analysismentioning
confidence: 99%
“…Exposure to reactive oxygen species (ROS) can lead to direct DNA damage, mutation, and carcinogenesis [6,7]. Previous studies have reported alterations in the concentrations of serum or neoplastic tissue trace elements in various carcinomas including breast, bladder, gastric, gallbladder, and lung cancers [1,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Most breast cancers initially develop as hormone-dependent cancer, which can later develop into a more hostile, hormone-independent tumor. A number of epidemiological studies have been carried out to understand the hormone-refractory breast cancer development, which evidenced the involvement of endocrine disruptors including trace elements [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%